1999
DOI: 10.1044/jslhr.4205.1249
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Verbal Working Memory Capacity in Children With Specific Language Impairment

Abstract: This study investigated verbal working memory capacity in children with specific language impairment (SLI). The task employed in this study was the Competing Language Processing Task (CLPT) developed by Gaulin and Campbell (1994). A total of 40 school-age children participated in this investigation, including 20 with SLI and 20 normal language (NL) age-matched controls. Results indicated that the SLI and NL groups performed similarly in terms of true/false comprehension items, but that the children with SLI ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
302
1
14

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 358 publications
(331 citation statements)
references
References 56 publications
14
302
1
14
Order By: Relevance
“…Hypothesis 1 predicted that children with SLI show decrements in listening span compared to their age-matched and language-matched peers. The listening span measures served to ensure that the SLI participants in this study show similar performance patterns to other reported data (e.g., Ellis-Weismer, Evans, & Hesketh, 1999, Marton & Schwartz, 2003Montgomery, 1995Montgomery, , 2000. The results of the listening span task are in line with previous findings.…”
Section: Discussionsupporting
confidence: 80%
“…Hypothesis 1 predicted that children with SLI show decrements in listening span compared to their age-matched and language-matched peers. The listening span measures served to ensure that the SLI participants in this study show similar performance patterns to other reported data (e.g., Ellis-Weismer, Evans, & Hesketh, 1999, Marton & Schwartz, 2003Montgomery, 1995Montgomery, , 2000. The results of the listening span task are in line with previous findings.…”
Section: Discussionsupporting
confidence: 80%
“…In the view of some authors (Adams & Gathercole, 2000), these children present an impairment in a system that specialises in holding material in memory for short periods of time (phonological short-term memory). Other authors believe that the deficit may affect the perception of auditory input more generally (Tallal, Stark, & Mellits, 1985), may be specific to certain grammatical difficulties (e. g. H. K. J. van der Lely, 1999) or may concern a more general processing or capacity limitation (Ellis Weismer, Evans, & Hesketh, 1999). These hypotheses seek to reflect the underlying neurodevelopmental factors thought to play a causal role in SLI.…”
Section: Cause Of Slimentioning
confidence: 99%
“…very young children (3 years) who do not initiate language acquisition normally (see for example, Fey & Loeb, 2002); teenagers (15-16 years) after several years of language remediation; children presenting a minor language disorder (-1 standard deviation for a language test battery, see Ellis Weismer, Evans, & Hesketh, 1999) or a more acute disorder (-1,5 standard deviation for a language test battery, see H. K. J. van der Lely & Ullman, 2001), or children presenting expressive (and receptive) disorders. Several linguistic tests have been proposed as potential psycholinguistic markers for such language disorders.…”
Section: Limits Of the Definition Of Slimentioning
confidence: 99%
“…This result is indicative of the type of learning difficulty children of this profile might face within real learning environments. From a theoretical perspective, these overall findings tie in with results of studies, which have demonstrated the difficulty of language-impaired children to create new referents ("fast-map"), as well as accurate phonological and semantic representations of novel words during controlled studies of quick incidental learning (QUIL) (Dollaghan, 1987;Ellis-Weismer et al, 1999;Gray et al, 2004;Oetting et al, 1994).…”
Section: Discussion and Future Perspectivesmentioning
confidence: 67%